(untitled) (Research, Society and Development, 2025)
Neonatal corneal opacity (NCO) is an ophthalmologic emergency that severely threatens visual development. Among its causes, obstetric trauma, particularly from forceps delivery, remains a significant, though decreasing, etiology. This trauma can cause a rupture in Descemet’s membrane (DM), leading to acute corneal edema, high astigmatism, and a profound risk of irreversible amblyopia. This narrative review aims to synthesize the most recent scientific evidence (2020-2024) on the approach to NCO, focusing on the clinical, imaging, and management findings that differentiate traumatic DM ruptures from their main clinical mimics. Methods: A narrative review was conducted, searching PubMed, SciELO, and LILACS for publications from 2020 to 2024 using relevant descriptors. Results: The synthesized literature indicates that any unilateral corneal clouding in a newborn with a history of instrumented delivery mandates urgent investigation. The classic differential diagnosis is primary congenital glaucoma (PCG). Clinical examination reveals that forceps-induced tears are typically vertical or oblique, whereas Haab’s striae (from PCG) are horizontal or circumferential. Tools like Anterior Segment Optical Coherence Tomography (AS-OCT) are essential for confirming the presence, location, and extent of the DM tear or detachment. Management is time-sensitive and ranges from conservative (topical hypertonics) to surgical (descemetopexy with air/gas) or, in refractory cases, keratoplasty (PKP or DSAEK). Conclusion: The approach to neonatal corneal opacity requires rapid etiological clarification. The ophthalmologist plays a central role in using clinical history and advanced imaging (AS-OCT) to distinguish traumatic from congenital causes, a distinction that dictates immediate management and the critical, long-term strategy for amblyopia prevention.